Application of Green Intellectual Property on Green Technology in Malaysia and Its Benefit: A Review of the Literature - Ridzuan, M.N.; Chew, B.C. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Intellectual property (IP) is commonly associated with a protection of an invention. Green IP exists not only due to the changing climate but also due to the sustenance of the global eco system. Developed countries such as Japan, United States, German and France have used the green intellectual property for their green technology protection. Hence, the Malaysian government should use this system as well. The objective of this paper is to analyse the implementation of Green IP in terms of social, economic and environmental aspects. The literature review consists of journals published within the year 2007 to 2017 to determine the meaning of Green IP and how it benefits Malaysia in terms of the social, economy and environmental aspects throughout the literature review. This study will enhance the development of Malaysia's standard in green technology and the development of nation growth.